Increasing Students’ Learning Outcomes through Cooperative Learning Model Mind Mapping Type - Muhammad Salman; Rahman Rahim (JELITA, 2021)
The purpose of this study is to find out how to apply the cooperative learning model, mind mapping type to improve the learning outcomes of elementary school students. This type of research is classroom action research which consists of two cycles which each cycle is carried out 3 times. The research procedure includes planning, implementing actions, observing and reflecting. The subjects in this study were 26 fourth grade students at SD Inpres Batanghari Jambi. The research result showed that in the first cycle, from 26 students, only 14 students completed individually, with an average score of 67.30. This has met the minimum completeness criteria or is in the moderate category, but this result does not meet the classical completeness criteria because only 53.85% of students have studied thoroughly, while the classical completeness that must be achieved is 85% of the total number of students. In cycle II, from 26 students, there were 24 students (92.31%) who met the minimum completeness criteria. Classically, it has also been fulfilled, namely the average value obtained is 80.19 or is in the high category. Based on the results of the analysis, it was concluded that the learning outcomes of fourth grade elementary school students through the application of the Mind Mapping cooperative learning model had increased.